Rozdział 2. La mediazione obbligatoria in Italia - Orrico, Lino (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
Mandatory mediation in Italy in civil and commercial matters is regulated by Legislative Decree 28/2010 and, over ten years, has undergone some changes dictated both by the legislator and following the observations of the Constitutional Court. Its application was also influenced by jurisprudence which decided on some aspects of interpretation of the law. Compulsory mediation, due to its strict link with the civil process, constitutes a complex procedure which, although autonomous, independent and characterized by confidentiality, must be conducted by observing the dictates of the law, in order to avoid the sanction of the inadmissibility of the subsequent judgment. As a mediation process, it also requires knowledge from the lawyers of negotiation and conflict management techniques. About mediation in Italy, the Ministry of Justice provides very complete statistical data, also in English.
Keywords: Legislative Decree 28/2010; mandatory mediation; mediation and jurisprudence; lawyers’ skills in mediation; mediation and civil process